Wittenberg's Wandering Spirits: Discipline and the Dead in the Reformation. Issue 3 (8th September 2015) - Unknown
Abstract : This article examines early protestant efforts to confront the belief that souls in purgatory appeared to or haunted the living. It demonstrates that a series of Articles on the Conjuration of the Wandering Dead (1521 or 1522) long attributed to Andreas Bodenstein von Karlstadt were actually written by Martin Luther or a close disciple. More importantly, it shows that these Articles participated in an extended effort by Luther to realize the doctrinal foci of the Reformation in the daily lives of believers as they encountered apparitions and poltergeists, worried about lost loved ones, and faced their own deaths. Luther aimed, in particular, to discipline Christians' senses of hearing and sight. Relating inward and outward senses, and explaining the apparent wandering dead as demons in disguise, Luther counseled Christians to hear the Word rather than the dead, to see Christ rather than the devil. Karlstadt also sought to realize doctrinal concentration, but in a manner shaped by his conception of faith as knowledge. Addressing anxiety about those who died before the Reformation, Karlstadt explained the wandering spirits as ignorant souls, destined for salvation but still needing to learn the right way. These wanderers spurred the living to diligent study of God's will.